Extrapancreatic necrosis without pancreatic parenchymal necrosis: a separate entity in necrotising pancreatitis?. Issue 10 (7th July 2012) - Bakker, Olaf J; van Santvoort, Hjalmar; Besselink, Marc G H; Boermeester, Marja A; van Eijck, Casper; Dejong, Kees; van Goor, Harry; Hofker, Sijbrand; Ahmed Ali, Usama; Gooszen, Hein G; Bollen, Thomas L; ,
Abstract : Objective: In the revised Atlanta classification of acute pancreatitis, the term necrotising pancreatitis also refers to patients with only extrapancreatic fat necrosis without pancreatic parenchymal necrosis (EXPN), as determined on contrast-enhanced CT (CECT). Patients with EXPN are thought to have a better clinical outcome, although robust data are lacking. Methods: A post hoc analysis was performed of a prospective multicentre database including 639 patients with necrotising pancreatitis on contrast-enhanced CT. All CECT scans were reviewed by a single radiologist blinded to the clinical outcome. Patients with EXPN were compared with patients with pancreatic parenchymal necrosis (with or without extrapancreatic necrosis). Outcomes were persistent organ failure, need for intervention and mortality. A predefined subgroup analysis was performed on patients who developed infected necrosis. Results: 315 patients with EXPN were compared with 324 patients with pancreatic parenchymal necrosis. Patients with EXPN less often suffered from complications: persistent organ failure (21% vs 45%, p<0.001), persistent multiple organ failure (15% vs 36%, p<0.001), infected necrosis (16% vs 47%, p<0.001), intervention (18% vs 57%, p<0.001) and mortality (9% vs 20%, p<0.001). When infection of extrapancreatic necrosis developed, outcomes between groups were equal (mortality with infected necrosis: EXPN 28% vs pancreatic necrosis 18%, p=0.16). Conclusion: EXPN causes fewer complications than pancreatic parenchymal necrosis. It should therefore be considered a separate entity in acute pancreatitis. Outcome in cases of infected necrosis is similar.